Inhibition of Myosin Light-Chain Kinase Enhances the Clearance of Lipopolysaccharide-Induced Lung Inflammation Possibly by Accelerating Neutrophil Apoptosis. Issue 3 (September 2017) - Shi, Wei; Xu, Chengyun; Hussain, Musaddique; Wu, Fugen; Lu, Meiping; Wu, Xiling; Tang, Lanfang; Wu, Ximei; Wu, Junsong
Abstract : ABSTRACT: Neutrophils are a population of inflammatory cells involved in acute lung injury (ALI), and lipopolysaccharide (LPS)–induced prolonged neutrophil survival and delayed neutrophil apoptosis hinder the alleviation of lung inflammation. Myosin light-chain kinase (MLCK) involved the RhoA/Rho kinase signaling pathway responsible for the cytoskeletal arrangement, and previous studies have revealed that inhibition of MLCK induces apoptosis in vitro and in vivo . In this study, glycogen-induced neutrophils isolated from rats or mice were incubated with ML-7, a MLCK-specific inhibitor, and LPS-induced ALI mice administrated with ML-7 were investigated, to demonstrate the roles of MLCK in neutrophil apoptosis as well as its possibility of contributing to the clearance of inflammation. We found that ML-7 dramatically promoted neutrophil apoptosis that possibly signal through the p38 to upregulate the expression of the apoptotic proteins caspase-9 and B-cell lymphoma 2 and to downregulate the expression of the antiapoptotic protein Bcl-2–associated X protein and myeloid cell leukemia-1. In mice, ML-7 accelerated the clearance of inflammation in LPS-induced ALI through attenuating neutrophil accumulation, histopathological changes, and pulmonary edema. ML-7 promoted elimination of inflammation possibly by accelerating neutrophil apoptosis and macrophage-mediated clearance. Moreover, ML-7 also reduced the LPS-induced production of proinflammatory cytokines interleukin-1β and tumor necrosis factor-α, and the activity of myeloperoxidase. Taken together, the present study uncovers a hitherto uncharacterized role of MLCK in neutrophil apoptosis that contributes to the alleviation of inflammation in response to LPS.